Vpliv kajenja na zdravilne učinkovine - Jakopin, Žiga (Farmacevtski vestnik, 2018)
Many potential interactions between smoking and drugs are known, which can be of pharmacokinetic as well as pharmacodynamic origin. most pharmacokinetic interactions occur due to the exposure to polycyclic aromatic hydrocarbons present in tobacco smoke, which act as potent inducers of liver CYP1A enzymes, in turn affecting drug metabolism. The pharmacodynamic interactions, on the other hand, are a result of pharmacological effects of nicotine. In this review, we focused primarily on providing a better insight into the mechanisms underlying the known pharmacokinetic and pharmacodynamic drug interactions with smoking. Finally, the reported case study of antipsychotic clozapine, provided an example of the importance of smoking status, focusing on smoking cessation as a risk factor, which can be easily overlooked by health care workers.
Keywords: farmakodinamične interakcije; farmakokinetične interakcije; Farmakokinetika; Kajenje; zdravilne učinkovine